Lead adsorption reactions on 3D macroassemblies of K-OMS-2 nanowire-based composite - Ng, Wee Kiat. (2013)
Lead is one of the most common available and prevalent heavy metals in the environment today. Due to its nature as a multi-organ system toxicant as well as its ability to effect chronic and acute problems to human health, especially in children, many researchers have placed an emphasis on finding better, more efficient whilst cheap methods of lead removal. Presently, adsorption by natural or synthetic materials has proven to be one of the most promising ways of achieving this objective. Given that many have reported the high adsorption affinity that lead has with oxides of manganese, this then sets the direction of this study. Currently, nanomaterials are being considered an exciting development in many fields of research due to their unique physiochemical properties. Such materials have gained recognition as being excellent for catalytic and adsorbent activity as compared to materials of the same make up at a normal scale. This enhanced activity has been attributed to the exponential increase in surface to mass ratio as the material shrinks in size. However, some researchers have highlighted the possible negative impacts of using nanomaterials. Current removal methods have proven to be ineffectual; either time or resource consuming, some have also reported concerns on the plausible toxicological effects that nanomaterials may have on human health.Given that such limitations on the use of nanomaterials may impede the development of a safe and cost-efficient adsorbent for lead remediation, this report proposes an innovative solution that employs the casting of 3D macroscopic devices from a K-OMS-2 nanowire-based composite for such purposes. The synthesis of the novel K-OMS-2 nanowire-based composite seeks to exploit the strength of the nanowire network structure for use as a building block on which nanoparticles that possess a high surface area can be embedded onto. The nanowire-based composite will then be casted into 3D macroscopic structures. This study will detail the fabrication process as well as the characterization of the nanowire-based composite and its constituent materials. An adsorption capacity study using the nanowire-based composite will be communicated in this report as well.